DC-Biased Optical OFDM for IM/DD Passive Optical Network Systems - SANYA, MAX FREJUS O.; DJOGBE, LÉOPOLD; VIANOU, Antoine; AUPETIT-BERTHELEMOT, Christelle (My University, 2015)
In the context of access networks, orthogonal frequency division multiplexing (OFDM) has been extensively studied for fiber-based optical communications. A DC-biased optical OFDM (DCO-OFDM) scheme (where no real constellation or Hermitian symmetry constraint is used), is proposed and explored for the first time, to the best of our knowledge, in an intensity modulated and direct detected (IM/DD) passive optical network (PON). In this paper, an analysis of the peak-to-average-power ratio and a discussion of the algorithm complexity are investigated. By means of numerical simulation in 12 Gb∕s next-generation (NG)-PON1 OFDM with a split ratio of 1∶64 users and 35 km reach, the new DCO-OFDM method is shown to achieve the same performance as the wellknown conventional DCO-OFDM but with less computational complexity (gain of almost 54.3% on the required operations per bit). As a result, the new DCO-OFDM seems very interesting and a good candidate for NG-PON costsensitive applications, considering the implementation of real-time demonstrators including digital modulators and demodulators based on digital signal processing or a field-programmable gate array (FPGA).
Keywords: Computational complexity; IM/DD fiber link; OFDM; Passive optical access networks